Comparative evaluation of ondansetron, palonosetron, and dexamethasone for antiemetic prophylaxis in cesarean section under spinal anaesthesia - Vankudoth Bhaskar; Jitendra Agrawal; Ankita Gupta; Ashish Mohan M (Asian Journal of Medical Sciences, 2025)
Background: Spinal anesthesia is the most common regional anesthesia used to provide surgical anesthesia for cesarean section. Nausea and vomiting are common symptoms experienced by patients undergoing cesarean section. Aims and Objectives: The aim of this study was to assess and compare the efficacy of dexamethasone, ondansetron, and palonosetron in prevention of nausea and vomiting. Materials and Methods: This prospective randomized study was conducted on total 90 patients undergoing cesarean section, divided in three groups of 30 patients each. Group O received 4 mg ondansetron i.v., Group P received palonosetron 075 mg i.v and Group D received 8 mg dexamethasone i.v. The incidence of nausea and vomiting was compared between the groups and side effects were assessed. Results: Antiemetic prophylaxis reduced the overall incidence of nausea and vomiting. However, Palonosetron had a lower incidence of nausea and vomiting as compared to dexamethasone and ondansetron. Conclusion: Our study concluded that Palonosetron had the lowest incidence of nausea and vomiting.